Diagnostic Validity Of Low Dose CT KUB In Demonstration Of Genitourinary Tract Calculi Compared To Normal Dose Ct Kub: A Provisional Study - Batool, Fizza; Rehman, Hina; Mughal, Hina Haneef; Rauf, Kashif; Zia, Khadija; Abbas , Farhat (Journal of Rawalpindi Medical College, 2023)
Objective: Renal colic is a common clinical condition. Our objective is to evaluate the diagnostic accuracy of low dose CT KUB for detection of urinary stones, to minimize radiation dose to the patients, and to analyze diagnostic accuracy of LDCT KUB in comparison to standard dose CT KUB. We speculate the LDCT KUB may reduce patient radiation dose while maintaining diagnostic value. Materials and Methods: This comparative cross sectional validation study was conducted at Department of Radiology in Benazir Bhutto Hospital, Rawalpindi June 2021 to Feb 2022. After approval of hospital ethical committee, a sample of 49 kidneys of 31 patients was collected by non-probability consecutive sampling technique. Included were the patients diagnosed with renal calculi referred from other departments. All the included patients were scanned by Toshiba Aquilion 16 slices, using automated tube current modulation, without any oral or IV contrast. CT scan started from diaphragm down to pubic symphysis with standard dose CT (SDCT) followed by low dose CT (LDCT). After the data was recorded, statistical package for social sciences, version 20.0 (SPSS Inc., Chicago, Illinois, USA) was used to analyse the data and generate results. Mean + standard deviation was calculated for qualitative data while frequency and percentage for qualitative variables. The means were compared by independent sample t test while the agreement between standard and low dose was depicted by kappa value. Results: A total of 49 kidneys of 31 patients with renal stones was included in this study. The mean age of the patients ranged from 27 years to 48 years with a mean of 36.42 + 9.97 year. In gender distribution, 75.5 % (37) were male while 24.5 % (12) were females. More than half 59 % (29) were right while 41 % (20) were left kidneys. Conclusion: This study demonstrated that LDCT was a productive and effective technique in the detection of urothelial stones despite considerable reduction in radiation dose and exposure as seen in SDCT.